A COMPARISON OF SERUM NUCLEAR FACTOR ERYTHROID 2-RELATED FACTOR 2 IN DIABETIC AND NON-DIABETIC PATIENTS WITH OSTEOARTHRITIS - Marwat, Zahid Irfan; Jadoon, Alamzeb; Nawaz, Shah; Sheharyar, Aamir; Khan, Saifoor Ahmad; Israr, Muhammad (Journal of Ayub Medical College Abbottabad, 2025)
Background: Osteoarthritis (OA) or inflammation of joints is a chronic degenerative and irreversible joint disorder. Oxidative stress in chronic inflammation contributes to osteoarthritis. Nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway have an inhibitory role in oxidative stress and inflammation, as significant interaction exists between transcriptional pathways involving Nrf2 and NF-κB which is related to immune response in body. Diabetes mellitus being a pro inflammatory condition, has more oxidative damage due to the effects of hyperglycaemia. This study evaluated serum Nrf2 expression levels in osteoarthritis patients in the presence and absence of hyperglycaemia in order to find out the magnitude of anti-oxidative response, whether Nrf2 expression levels increases or decreases in oxidative stress environment comparatively. Objectives of this study were to evaluate Nrf2 serum expression levels in osteoarthritis patients by ELISA and to compare Nrf2 serum circulatory levels between diabetic osteoarthritis patients’ group and non-diabetic osteoarthritis patients’ group. Method: The comparative cross-sectional study was conducted from February 01, 2023 to 31 January, 2024 at department of Biochemistry, Nowshera medical college (NMC), Nowshera and Medicine/Orthopaedic OPD of Qazi Husain Ahmad Medical complex (QHAMC), Nowshera. This comparative cross-sectional study included 44 male and female osteoarthritis patients of ≥50 years old that were further divided into a diabetic and non-diabetic group on the basis of hyperglycaemia. NRF2 levels were measured using ELISA. Results: Blood circulatory levels of NRF2 were significantly higher in non-diabetic patients of osteoarthritis Conclusion: Nrf2 levels are lower in diabetic patients of osteoarthritis as compared to non-diabetic patients of osteoarthritis.